Less Severe Cases of COVID-19 in Sub-Saharan Africa: Could Co-infection or a Recent History of Plasmodium falciparum Infection Be Protective? - Kalungi, Allan; Kinyanda, Eugene; Akena, Dickens Howard; Kaleebu, Pontiano; Bisangwa, Innocent M. (Frontiers in Immunology, 2021)
The sub-Saharan African region has generally experienced less severe cases of coronavirus disease 2019 (COVID-19). In addition to other potential explanations for less severe cases of COVID-19 such as the population socio-demographics, we hypothesize in this mini review that individuals with a recent history of malaria infection may be protected against infection or severe form of COVID-19. Given that both SARS-CoV-2 and Plasmodium falciparum merozoites bind to the cluster of differentiation CD147 (CD147), we hypothesize that the immunological memory against Plasmodium falciparum merozoites primes SARS-CoV-2 infected cells for early phagocytosis, hence protecting individuals with a recent Plasmodium falciparum infection against COVID-19 infection or severity.. This mini review therefore discuss the potential biological link between Plasmodium falciparum infection and COVID-19 infection or severity and further highlight the importance of CD147 immunoglobulin as an entry point for both SARS-CoV-2 and Plasmodium falciparum into host cells.